Lessons Learned from Surveillance of Antimicrobial Susceptibilities of Pseudomonas aeruginosa at a Large Academic Medical Center - Brett H. Heintz; Jenana Halilovic (MDPI AG, 2010)
This research report assessed the differences in resistance rates and antimicrobial usage-versus-susceptibility relationships of Pseudomonas aeruginosa found in various hospital patient care areas. A simplified case control study was also performed to identify patient-specific risk factors associated with cefepime-resistant P. aeruginosa isolates. Last, we determined the consequence of combining mucoid and non-mucoid derived antimicrobial susceptibilities of P. aeruginosa into hospital antibiograms. Overall, susceptibility rates remained lower in the intensive care units (ICUs) compared to the non-ICU patient care areas, except for cefepime over the last time period. Cefepime utilization and antimicrobial-resistance rates among P. aeruginosa isolates had a significant relationship. Decreased meropenem exposure was associated with lower resistance rates relative to cefepime. Risk factors independently associated with cefepime-resistant P. aeruginosa were structural lung disease, ICU admission, recent third generation cephalosporin use, frequent hospital admission and non-urine isolates. Large and statistically significant differences were observed between non-mucoid and combined percent susceptibility data for aminoglycosides. To control antimicrobial resistance and optimize initial empiric antimicrobial therapy, antimicrobial susceptibility and utilization patterns in specific patient care areas should be monitored and risk factors for antimicrobial resistance should be assessed. Mucoid strains of P. aeruginosa should not be included into antimicrobial susceptibility data as this may underestimate activity of most antipseudomonal agents.